High mannose-specific lectin (KAA-2) from the red alga Kappaphycus alvarezii potently inhibits influenza virus infection in a strain-independent manner - Sato, Yuichiro (Biochem Biophys Res Commun, 2011)
The carbohydrate binding profile of the red algal lectin KAA-2 from Kappaphycus alvarezii was evaluated by a centrifugal ultrafiltration–HPLC method using pyridylaminated oligosaccharides. KAA-2 bound exclusively to high mannose type N-glycans, but not to other glycans such as complex type, hybrid type, or the pentasaccharide core of N-glycans. This lectin exhibited a preference for an exposed α1–3 Man on a D2 arm in a similar manner to Eucheuma serra agglutinin (ESA-2), which shows various biological activities, such as anti-HIV and anti-carcinogenic activity. We tested the anti-influenza virus activity of KAA-2 against various strains including the recent pandemic H1N1-2009 influenza virus. KAA-2 inhibited infection of various influenza strains with EC(50)s of low nanomolar levels. Immunofluorescence microscopy using an anti-influenza antibody demonstrated that the antiviral activity of KAA-2 was exerted by interference with virus entry into host cells. This mechanism was further confirmed by the evidence of direct binding of KAA-2 to a viral envelope protein, hemagglutinin (HA), using an ELISA assay. These results indicate that this lectin would be useful as a novel antiviral reagent for the prevention of infection.